2007
DOI: 10.1111/j.1464-5491.2007.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

A low‐carbohydrate diet is more effective in reducing body weight than healthy eating in both diabetic and non‐diabetic subjects

Abstract: The diet was equally effective in those with and without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 21 publications
3
93
0
2
Order By: Relevance
“…All subjects gave written informed consent. Twenty-six overweight or obese [body mass index (BMI) Ͼ25 kg/m 2 ] individuals were randomly allocated to a low-carbohydrate (Յ40 g carbohydrate/d) (n ϭ 12) or a healthy eating diet (n ϭ 14) for 3 months as previously described (19). Exclusion criteria included pregnancy, history of eating disorders, alcohol or drug abuse, serum creatinine above 150 mmol/liter, abnormal liver function tests (Ͼ1.5 ϫ upper limit of reference interval), and known malignancy.…”
Section: Groupmentioning
confidence: 99%
“…All subjects gave written informed consent. Twenty-six overweight or obese [body mass index (BMI) Ͼ25 kg/m 2 ] individuals were randomly allocated to a low-carbohydrate (Յ40 g carbohydrate/d) (n ϭ 12) or a healthy eating diet (n ϭ 14) for 3 months as previously described (19). Exclusion criteria included pregnancy, history of eating disorders, alcohol or drug abuse, serum creatinine above 150 mmol/liter, abnormal liver function tests (Ͼ1.5 ϫ upper limit of reference interval), and known malignancy.…”
Section: Groupmentioning
confidence: 99%
“…Ketogenic diets at a very low carbohydrate content (VLCKD), as well as having proven benefits for weight loss [80][81][82][83][84][85][86][87] and on cardiovascular disease risk factors [44,45,65,80,81,84,[88][89][90][91][92][93][94][95][96][97][98] , could also be useful nutritional tools in the hands of the medical practitioner, together with other nutritional aids such as use of omega-3 fatty acids [99][100][101][102][103][104][105] . We believe that there are well-founded physiological and biochemical bases that support their use for limited time periods (30-60 days) with the aim of reducing the pathogenic mechanisms underlying acne vulgaris and restoring a proper hormonal status.…”
Section: Discussionmentioning
confidence: 99%
“…Six randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate in relation to glycosylated haemoglobin proteins, five of which were included in the meta-analysis (Wolever & Mehling, 2003;Seshadri et al, 2005;Claessens et al, 2009;Frisch et al, 2009;Sloth et al, 2009). One trial could not be included in an analysis because it did not provide any measures of variation (Dyson et al, 2007). One trial was subsequently identified in the update search (Weickert et al, 2011 …”
Section: Insulin Resistance/sensitivitymentioning
confidence: 99%
“…The outcomes examined were fasting total cholesterol, LDL-cholesterol, HDL-cholesterol, triacylglycerol, total cholesterol: HDL-cholesterol ratio, LDL-cholesterol: HDL-cholesterol ratio. For fasting total cholesterol concentration, ten trials could not be included in a meta-analysis (Peterson & Jovanovic-Peterson, 1995;Wolever & Mehling, 2002;Drummond et al, 2003;Foster et al, 2003;O'Brien et al, 2005;Johnston et al, 2006;Dyson et al, 2007;Kirkwood et al, 2007;Dale et al, 2009;Layman et al, 2009) (Cardio-metabolic review, the hyperlipidaemias and blood lipids chapter p 65-70). For fasting LDL-cholesterol concentration, six trials could not be included in a meta-analysis (Wolever & Mehling, 2002;Johnston et al, 2006;Kirkwood et al, 2007;Dyson et al, 2007;Lasker et al, 2008;Layman et al, 2009) and for triacylglycerol concentration, eight trials could not be included in a meta-analysis (Peterson & Jovanovic-Peterson, 1995;Wolever & Mehling, 2002;Johnston et al, 2006;Kirkwood et al, 2007;Dyson et al, 2007;Lasker et al, 2008;Dale et al, 2009;Layman et al, 2009) (Cardio-metabolic review, the hyperlipidaemias and blood lipids chapter p 122-162).…”
Section: 30mentioning
confidence: 99%
See 1 more Smart Citation